Experimental and Numerical Investigations of a Dual-Shaft Test Rig with Intershaft Bearing. (5th April 2007) - Guskov, M.; Sinou, J.-J.; Thouverez, F.; Naraikin, O. S.
Abstract : This paper deals with an experimental study of a dual rotor test rig. This machine, which was developed and built at the Laboratoire de Tribologie et Dynamique des Systèmes, Ecole Centrale de Lyon, will be first presented. It is composed of two coaxial shafts that are connected by an intershaft bearing and rotate independently, each one driven by its own motor. Their lateral vibrations and whirling motion are coupled by the intershaft bearing. The experimental tests consisting in run-ups and the associated measured unbalance response of the dual rotor will be investigated. The influence of the rotation of each rotor on the critical speeds and the associated amplitudes will be discussed. Moreover, this paper presents a numerical model of the dual rotor. Correlations between the experimental and numerical tests will be investigated. The objective is to be able to predict phenomena observed in experiments, starting from a rather fine numerical model.